AN IMPLEMENTATION OF BEHAVIOUR-BASED NAVIGATION ROBOT USING FUZZY LOGIC ON AN INDOOR MOBILE ROBOT - SYED PUTRA AL-IDRUS, SYED FIZUAN AL-IDRUS (IRC, 2019)
From the continued development of autonomous driving vehicle, it became more apparent that this technology is desire by everyone to reduce the number of accidents causes by human error. In behavior-based navigation the vehicle can operate on its own while also able to react with the surrounding environment. A few methods to implement to behavior-based navigation is with wall-following, line- following with a fuzzy logic as the controller. The issue with behavior-based navigation it still requires a lot of study to ensure that it a reliable to be use more prominently. For this study a fuzzy logic algorithm will act as the controller while having wall-following to help it navigate the environment and will be implemented on a two-wheel mobile robot to observe the performance and reliability of the mobile robot in an indoor test area with obstacles. The benefits for using behavior-based navigation is that there isn’t a required to create a map area for the controller as behavior-based navigation will react to the environment. Currently, the fuzzy logic algorithm with a wall following navigation has been implemented on a two-wheel mobile robot and have begun initial testing